Diagnostic Utility of Fine Needle Aspiration Cytology in Oral Cavity and Oropharyngeal Lesions - Acharya, Subarna (Journal of Nepalgunj Medical College, 2018)
Fine needle aspiration cytology is being commonly used for initial diagnoses of oral cavity and oropharyngeal lesions. The aim of this study was to assess the role of Fine Needle aspiration cytology in diagnosis of intraoral and oropharyngeal lesions and to compare with histopathological findings in those cases which underwent biopsy examination. This is a tertiary care center based retrospective study done over a period of two years. Out of total 660 fine needle aspiration cytology in two years; 133 cases were of oral and oropharyngeal region. 54 were male and 79 were of female. Frequently involved site was tongue (n=45). Predominant non neoplastic cases were of chronic inflammation (n=43) and neoplastic cases of squamous papilloma (n=15). Among neoplastic cases most common malignant cases were of squamous cell carcinoma (n=4). Sensitivity of the FNAC method was found to be 80% and specificity was identified as 100% comparing with gold standard histopathological examination. No significant complications were seen in patients undergoing these FNAs. It can be concluded that FNA is a simple and rapid diagnostic test that can be useful for preliminary assessment of oral and oropharyngeal lesion.